An investigation into the material efficiency practices of UK manufacturers - Abdul Rashid, Salwa Hanim (Cranfield University, 2009)
This thesis examines the Material Efficiency practices of manufacturing companies in the UK. The study was motivated by the increasing attention given by literature to sustainable strategies in general, with less attention being given to material resources which in turn contributes to the reduced supply of natural resources, persistent solid waste and toxicity. There is also a lack of insight about how the manufacturing industry is coping with pressures to reduce solid waste and better utilise materials as resources. A critical literature review identifies Material Efficiency and related strategies and any issues of implementation. This academic perspective is supported by an exploratory study of Material Efficiency practices using multiple case studies and qualitative data collection and analysis. The participating companies selected were manufacturing companies that practice Material Efficiency and any related strategies. It was found that manufacturers do practice Material Efficiency and related strategies although few of them use the names and constructs found in the literature. Most of the companies do practice the lowest strategy (e.g. Waste Minimisation) in the sustainable manufacturing hierarchy, while most companies struggle with developing the higher strategies such as Resource Efficiency and Eco-efficiency, in part due to measurement complexity. The investigation found a set of attributes in the difficulties, benefits and accelerators that affect manufacturers when implementing Material Efficiency strategies and also studied the factors that motivated the manufacturers to implement and to choose the strategies. It is found from this research that these attributes are interrelated and dependent on each company’s context such as company’s size, type of product, and type of materials used etc. The findings describe real Material Efficiency practices as used inside the UK manufacturing industry, while comparing actual practice to what has been suggested in the literature. The study provides insight into how companies experience and practice Material Efficiency and other related sustainable manufacturing strategies.